A coupled hydro-sediment-ecological modeling approach to simulating ecological dynamics in the large reservoir system of Southwest China - Longhu Yuan; Jiamei Zhang; Yuning Tan; Huaixiang Liu; Yubin Chen; Yongjun Lu; Zhili Wang (CATENA, 2026)

Enhanced phosphate capture driven by collaboration of diversified active sites in zirconium alginate immobilized LaAl bimetallic organic framework - Yuning Chen; Yunrong Xu; Ruoting Gao; Yuechi Lin; Yilin Liu; Chaohai Wei; Moses Basitere; Guanglei Qiu (Desalination, 2026)

Evolution of pore structure and fractal characteristics during hydrate-based CO2 sequestration in unconsolidated sediments - Zhun Zhang; Yuning Liu; Yunkai Ji; Jiaxian Wang; JinQiu Hu; Bin Fang; Wanjun Lu; Changling Liu; Fulong Ning (Chemical Engineering Journal, 2026)

Evolution of water and sediment inflows to the largest reservoir system in Southwest China: Historical patterns and future predictions - Yuning Tan; Wenjie Li; Huaixiang Liu; Hongbo Du; Yu Wan (CATENA, 2026)

Estimation method for icing distribution along a railway catenary using CNN-SimAM-PINN hybrid deep learning - Yuning Wang; Lijun Zhou; Bokai Liu; Bin Tong; Yuqing Xie; Huajun Guan; Yijie Zhou; Dongyang Wang; Lei Guo; Liqing Zhang (Cold Regions Science and Technology, 2026)

Differentiated interfacial regulation by a bio-based polysaccharide depressant for sustainable Cu–Mo flotation separation - Yimin Zhu; Yuning Ma; Hui Li; Wenjie Han; Jie Li; Jie Liu (Minerals Engineering, 2026)

A comprehensive distributed hydrological framework for assessing flood responses to environmental change under multiple human disturbances - Yuhao Wang; Ke Zhang; Edwark Park; Yuning Luo; Jie Liu; Shunzhang Li; Zhaoan Zhang; Yue Kong; Sheng Wang (Journal of Hydrology, 2026)

Silicon-mediated stoichiometric controls on phytoplankton community shifts in the Yangtze and Yellow Rivers - Li Yingxiao; Chi Yuning; Zhong Xiaosong; Liu Xiaotian; Lv Zongqing; Wu Wentao; Ran Xiangbin (Journal of Hydrology, 2026)

Construction of a heterojunction based on polyphthalocyanine and defective ZnIn2S4 for enhanced CO₂ photoreduction performance - Yuxuan Liu; Yuning Liang; Weimeng Chi; Shuohui Li; Yanhua Gao; Ying Chen (Journal of Environmental Chemical Engineering, 2026)

Self-catalytic oxidation enables metal recovery from copper smelting flue dust - Zhiqiang Liu; Hao Du; Feifei Hu; Shaona Wang; Muneeb UI Hassan Naseer; Yuning Guo; Yeqing Lv; Biao Liu (Journal of Hazardous Materials, 2026)

Mitochondrial pathway-mediated gut cell apoptosis: A key mechanism of nitenpyram toxicity in Diaphorina citri adults - Yuning Li; Huyin Hu; Huanqian Yao; Xinyi Xie; Shuyin He; Cuiting Liu; Veeran Sethuraman; Hanhong Xu; Zhongzhen Wu; Benshui Shu (Journal of Asia-Pacific Entomology, 2026)

Canopy vertical and horizontal structures shape understory plant diversity in natural and planted forests on the loess plateau - Zijian Shangguan; Yuning Wang; Jingyi Qin; Zhuo Liu; Hang Yu; Tianjiao Feng; Chao Wang; Tao Lang; Ping Wang (Plant and Soil, 2026)

Targeting Eustachian Tube Microenvironment: Probiotic Surfactant Utilization for Antimicrobial Peptide Secretion to Prevent Otitis Media - Xichu Duan; Yuning Xing; Wenwen Liu; Li Li (Probiotics and Antimicrobial Proteins, 2026)

Pressure and Permeability Evolution near Hydrate Exploitation Well During Constant-Rate Water Flooding: An Experimental Study - Yuning Liu; Yunkai Ji; Qiang Fu; Zhenyu Zhu; Zihao Wang; Gaowei Hu; Qiang Chen; Yongchao Zhang; Qingtao Bu; Yizhao Wan (Journal of Marine Science and Engineering, 2026)
Dynamic damage to the seepage characteristics of the near-well zone during natural gas hydrate exploitation is a key factor limiting production stability. There is still a lack of systematic understanding of the microscopic mechanisms underlying fine-particle migration and blockage in the near-well zone. In this study, a long sand-packed column was segmentally packed with clayey-silt sediments from the South China Sea and quartz sand to simulate the near-well reservoir and the packed layer, respectively. Long-term seepage processes in the near-well zone were simulated using water flow experiments at constant flow velocities. By combining pressure distribution monitoring with particle-size analysis, the spatiotemporal evolution of seepage characteristics in the near-well zone is revealed from both macroscopic and microscopic perspectives. Results indicate that under long-term displacement, the reservoir permeability near the injection end increased from 0.0149 mD to 0.0159 mD; the reservoir permeability near the packed layer exhibits the greatest decline, dropping from 0.0089 mD to 0.0065 mD. Combined with the particle-size analysis of the packer layer, the boundary between the reservoir and the packed layer is identified as the critical site for permeability damage in the near-well zone. Radial flow inversion shows that a reduction in wellbore radius leads to an increase in reservoir pressure, with the increase being greater the farther from wellbore. A decrease in the permeability of packed layer causes an increase in reservoir pressure, but the magnitude of the increase is consistent across different locations. It provides a theoretical basis for the optimized design of production wells.

Mangrove-inspired salt-excreting evaporator for enhanced solar desalination and mineral salt harvesting - Dengkai Xu; Jin Yang; Lixuan Zhao; Xiayuan Zhang; Yuning Liu; Xiaohua Jia; Haojie Song (Desalination, 2026)

Brønsted base-pillared cobalt-nickel layered double hydroxides for aqueous calcium-ion batteries - Mengting Shen; Yuning Peng; Xin Wang; Huan Liu; Xiang Cai (Chemical Engineering Journal, 2026)

Effects of unsteady leading-edge cavitation on hydrofoil modal behavior and DMD-resolved flow structures - Siyuan Liu; Hao Zhou; Meng Wen; Yongshun Zeng; Zhifeng Yao; Yuning Zhang (Ocean Engineering, 2026)

Coaxial electrospun TiO2@CuO heterojunctions with interfacial charge rearrangement for photothermal oxidation of toluene - Weimin Huang; Ke-Xin Li; Shuzhuo Bai; Shanshan Chen; Fanbin Meng; Bing Qin; Yuning Yang; Zonghui Liu; Wen-Tao Zheng; Zhun Hu (Journal of Environmental Chemical Engineering, 2026)

In situ preparation of heterometallic polyphthalocyanine/ZnIn2S4 heterojunction for efficient photocatalytic CO2 reduction - Yuxuan Liu; Yuning Liang; Weimeng Chi; Shuohui Li; Yanhua Gao; Ying Chen (Environmental Research, 2026)

Isolation and Cytotoxic Activities of Two New 2-Pyridone Alkaloids with Unique Structures from the Beibu Gulf Coral-Derived Acremonium sclerotigenum GXIMD 02501 - Yuning Qin; Xinjian Qu; Miaoping Lin; Hong Zhang; Huangxue Qin; Chenghai Gao; Yonghong Liu; Xuefeng Zhou; Xiaowei Luo (Journal of Ocean University of China, 2026)

Reproductive toxicity mechanisms of PNMC: Evidence from mitochondrial dysfunction and hormone synthesis disruption in the KGN cells - Jingyi Xie; Zixuan Pan; Yuhan Du; Kexue Li; Yuning Liu; Qiang Weng; Haolin Zhang (Reproductive Toxicology, 2026)

Efficacy of traditional Chinese Medicine and antibiotics for bovine mastitis: A meta-analysis - Yang Ni; Huanqi Liu; Cailin Xu; Zhenbang Ye; Xueshu Han; Yuning Liu; Zhenjun Sun; Yongping Chen (Preventive Veterinary Medicine, 2026)

Development and testing of a scaled floating wind turbine in the wind tunnel for dMATCH framework - Yuning Gao; Xinliang Tian; Yitang Liu; Xin Li; Peng Wang; Binrong Wen; Eddie Yin Kwee Ng (Ocean Engineering, 2026)

Quercetin glycoside-incorporated lipid nanoparticles for mRNA delivery exhibit reduced inflammatory response - Yujing Shen; Yuning Wei; Weizhao Weng; Chunxia Yang; Chuanjun Wu; Xuyuan Liu; Xishan Xu; Jianping Qi; Wei Zhang; Ning Ding (Chemical Engineering Journal, 2026)

Structural control of nitrogen-doped carbon nanotubes embedded with magnetic nanoparticles enabling tunable electromagnetic response and multifunctional flexible film - Jiantao Sun; Kexin Jin; Jing Wang; Xueai Li; Yue Li; Yuning Shi; Chunsheng Wang; Wanchun Guo; Kesong Tian; Haiyan Wang; Yingdan Liu (Chemical Engineering Journal, 2026)

Microplastics modulate triclosan abiotic methylation: Effects of polymer type and photoaging - Yuning Qian; Xue Zhang; Chunzhao Chen; Jian Tang; Yujiao An; Jianjie Chen; Qianxin Zhang; Bin Liu; Shan Niu; Gang Yu (Journal of Hazardous Materials, 2026)

Unit-level stranded asset of coal power under low-carbon transition pathways toward China's carbon neutrality - Yanhua Wang; Yuning Zhang; Ke Wang; Junling Liu; Xunzhang Pan (Energy Policy, 2026)

Metals/Metalloids Profile in Seminal Plasma/Serum of Patients with Asthenozoospermia/Oligozoospermia: Correlation with Semen Quality - Yang Wang; Shiyuan Zhao; Yuning Liu; Junbo Zhang; Longqiao Cao; Pei Jiang; Yanyan Qiao (Biological Trace Element Research, 2026)

Influence of spring soil moisture in the central and western Tibetan Plateau on the thermal conditions of underlying surface - Shanshan Zhong; Yumeng Liu; Yuning Xia; Xinchang Zhang (Climate Dynamics, 2026)

Telomere-to-telomere genome assembly reveals the genomic architecture of disease resistance and yield coordination in elite wheat YM33 - Guofeng Lv; Yating Wang; Heping Zhang; Yuning Shen; Wenjing Hu; Datong Liu; Mengmeng Liu; Wenna Wang; Yuwen Gao; Caixia Lan; Tongde Bie; Hongya Wu; et al. (Molecular Plant, 2026)

Photocatalytic-peroxymonosulfate dual activation strategy: Efficient removal of norfloxacin by Z-type heterojunction CoWO4/α-Fe2O3 composite catalyst - Jian Zhang; Xinyan Wang; Zixin Liu; Xin Cheng; Haina Bai; Yuning Zhang; Ruoyi Li (Journal of Environmental Chemical Engineering, 2026)

Performance evaluation of sustainable development goals (SDGs) for Chinese major coastal cities: A spatially explicit evaluation considering evenness - Chao Liu; Ping Li; Yuning Zhao; Zhiwei Zhang (Ocean & Coastal Management, 2026)

GHydroMod-SIM-DAI v1.0: A new distributed hydrological model capable of dynamically recognizing runoff generation mechanisms and accounting for aboveground and underground anthropogenic impacts - Yuhao Wang; Ke Zhang; Yuning Luo; Qinuo Zhang; Zhijia Li; Cheng Yao; Xinyu Chen; Sheng Wang; Jie Liu; Chuntang Zhang; Shunzhang Li (Journal of Hydrology, 2025)

γ-Aminobutyric acid and fat alter soymilk gel properties and functionality via protein remodeling - Kangyong Zhang; Hongwei Tang; Yuning Yang; Zhongjiang Wang; Bailiang Li; Fei Liu (Food Chemistry, 2025)

Improvement of methane production from waste activated sludge by ultrasound-activated peracetic acid oxidation - Hui Wang; Xuecheng Li; Yuning Yang; Yufen Wang; Tingting Zhu; Peizhe Sun; Bing-Jie Ni; Yiwen Liu (Chemical Engineering Journal, 2025)

Dual-functional 3D-printed polyetheretherketone scaffolds with immunomodulatory nano‑calcium silicate/interleukin-4 coating synergistically enhance osteogenesis through macrophage M2 polarization and NF-κB pathway suppression - Xiaoyu Guo; Yanwen Su; Zixuan Wu; Zidong Wu; Kaili Liu; Junyu Yue; Yuning Qu; Kunzheng Wang; Jiankang He; Rui Ma; Pei Yang (Chemical Engineering Journal, 2025)

Predicting the effects of microplastics on soil properties using machine learning - Xudong Xu; Wenhao Li; Yuning Wang; Xu Zhao; Yu Wang; Lei Wang; Hongwen Sun; Chunguang Liu (Applied Soil Ecology, 2025)

Tire wear particle leachate induces lipid metabolism disorders in Procambarus clarkii, leading to liver inflammation and mitochondrial dysfunction in hepatocytes - Xianghan Liu; Qichen Jiang; Wenzong Zhou; Muyan Li; Chenxi Zhu; Quan Yuan; Yuning Zhang; Hang Yang; Weiwei Huang; Weiwei Lv (Marine Pollution Bulletin, 2025)

Reducing dye pollution: Sustainable reuse of colored cotton waste powders in washing-free flat screen printing - Chengyong Gao; Yuning Liu; Tieling Xing; Xiao Li; Sheng Shi (Sustainable Chemistry and Pharmacy, 2025)

Study on mechanism of in-situ hydrogen generation based on molecular dynamics simulation from pyrolysis of heavy oil - Houfeng He; Yuning Gong; Mingguo Peng; Haoran Zheng; Tian Feng; Ming Zhang; Qiu Li; Pengcheng Liu (Fuel, 2025)

Preparation of superhydrophilic functionalized nZVI-MOF-74(Co)-PDA@PVDF composite membranes for enhanced Cr(VI) removal - Mingchun Bi; Yuning Liang; Weimeng Chi; Yuchao Cui; Yuxuan Liu; Juan Ren; Ying Chen (Environmental Research, 2025)

Livestock grazing increases soil bacterial alpha-diversity and reduces microbial network complexity in a typical steppe - Yiyang Zhao; Zhaokai Sun; Chengyang Zhou; Yong Ding; Yiran Zhang; Yuning Liu; Li Liu (Agriculture, Ecosystems & Environment, 2025)

Combined transcriptome and metabolome analyses provide insights into host adaptation mechanism of Spodoptera frugiperda to cruciferous vegetables - Benshui Shu; Yuning Li; Cuiting Liu; Junying Wu; Cuiling Ye; Jintian Lin; Jingjing Zhang (Journal of Insect Physiology, 2025)

Identification and utilization of a novel large-effect QTL and linked markers for enhancing protein concentration in peanut - Mingjun Wang; Jianbin Guo; Gaorui Jin; Taihua Yang; Weigang Chen; Yuning Chen; Li Huang; Huaiyong Luo; Xiaojing Zhou; Boshou Liao; Huifang Jiang; Nian Liu; et al. (Theoretical and Applied Genetics, 2025)

Revolutionary photoelectrochemical water splitting performance of BiVO₄/Bi₂S₃ heterojunction photoanodes boosted by trace bio-Cr₂O₃ through multiple mechanisms - Yefei Su; Yang Yu; Tingting Xue; Kai Teng; Yuning Fan; Jiangjun Lin; Chang Liu; Qing Qu; Lei Li (Chemical Engineering Journal, 2025)

Regional Wave Spectra Prediction Method Based on Deep Learning - Yuning Liu; Rui Li; Wei Hu; Peng Ren; Chao Xu (Journal of Marine Science and Engineering, 2025)
The wave spectrum, as a key statistical feature describing wave energy distribution, is crucial for understanding wave propagation mechanisms and supporting ocean engineering applications. This study, based on ERA5 reanalysis spectrum data, proposes a model combining CNN and xLSTM for rapid gridded wave spectrum prediction over the Bohai and Yellow Seas domain. It uses 2D gridded spectrum data rather than a spectrum at specific points as input and analyzes the impact of various input factors at different time lags on wave development. The results show that incorporating water depth and mean sea level pressure significantly reduces errors. The model performs well across seasons with the seasonal spatial average root mean square error (SARMSE) of spectral energy remaining below 0.040 m2·s and RMSEs for significant wave height (SWH) and mean wave period (MWP) of 0.138 m and 1.331 s, respectively. At individual points, the spectral density bias is near zero, correlation coefficients range from 0.95 to 0.98, and the peak frequency RMSE is between 0.03 and 0.04 Hz. During a typical cold wave event, the model accurately reproduces the energy evolution and peak frequency shift. Buoy observations confirm that the model effectively tracks significant wave height trends under varying conditions. Moreover, applying a frequency-weighted loss function enhances the model’s ability to capture high-frequency spectral components, further improving prediction accuracy. Overall, the proposed method shows strong performance in spectrum prediction and provides a valuable approach for regional wave spectrum modeling.

Automated evaluation of dairy goat body condition and analysis of differences in lumbar features, milk composition and blood biochemical indicators - Yuning An; Yifeng Song; Ziqi Meng; Yuan Wang; Buyu Wang; Na Liu; Jingwei Qi; Ming Xu; Xiaoping An (Small Ruminant Research, 2025)

The influence of γ-aminobutyric acid production and fat content on the gel properties, protein conformation, and nutritional characteristics of fermented milk: Achieved through interactions with milk proteins - Kangyong Zhang; Yang Cheng; Yuning Yang; Yuxing Li; Bailiang Li; Fei Liu (Food Chemistry, 2025)

Identification of candidate genes associated with resistance to aflatoxin production in peanut through genetic mapping and transcriptome analysis - Dongxin Huai; Li Huang; Xiaomeng Xue; Bolun Yu; Yingbin Ding; Gaorui Jin; Hao Liu; Manish K. Pandey; Hari Kishan Sudini; Huaiyong Luo; Xiaojing Zhou; Nian Liu; et al. (Theoretical and Applied Genetics, 2025)

Evaluating the cumulative impacts of multiple stressors on marine and coastal ecosystems in China's marine waters - Chao Liu; Ping Li; Yuning Zhao; Dahai Liu; Shuo Wang (Environmental Impact Assessment Review, 2025)

Z-type ZnIn2S4 homojunction for high performance photocatalytic hydrogen evolution - Wenbo Wang; Jie Liu; Mengxia Cui; Xinghua Li; Luyao Niu; Xi Wu; Yuning Chen; Xiaowei Li; Hancheng Zhu; Dan Wang; Changlu Shao (Chemical Engineering Journal, 2025)

Optimizing a link-based travel incentive scheme integrating personal carbon trading for low-carbon commuting - Bing Liu; Xiaolei Ma; Yuning Shi; Xiaohai Liu; Kun Gao; Qiong Tian; Wenwei Wang (Journal of Environmental Management, 2025)

Polyvinylimidazolium/polyacrylonitrile nanofiber separator with enhanced polysulfide adsorption toward durable lithium–sulfur batteries - Ping Feng; Chenxiao Lin; Fang Chen; Yiwei Gao; Yuning Fang; Yong Zheng; Yan Yan; Mingkai Liu (Chemical Engineering Journal, 2025)

Epithelial-mesenchymal transition during the growth and involution of the prostate gland in wild ground squirrels (Spermophilus dauricus) - Pengyu Chen; Xinyue Hu; Qingjing Gao; Yue Zhou; Wenjing Lu; Xingye Zhang; Maria Daniela Artigas Ramirez; Yingying Han; Zhengrong Yuan; Yuning Liu; Qiang Weng; Haolin Zhang (Animal Reproduction Science, 2025)

dMATCH: A novel integrated testing method for floating wind turbine dynamics – Potential error and its impact - Yuning Gao; Xinliang Tian; Guangqi Liu; Zhihao Jiang; Da Li; Tao Peng; Guiyong Zhou; Binrong Wen (Ocean Engineering, 2024)

Green algal polysaccharides and derivatives as potential therapeutics for metabolic diseases - Yusong Qiu; Zhengxin Chen; Yiqi Zhu; Jiahui Wen; Yuxi Wen; Yuning Liu; Weichao Chen; Chao Zhao (Food Bioscience, 2024)

Enhanced removal of Cr(VI) from aqueous solutions using a zero-valent nickel/iron-PDA@PVDF membrane prepared via a simple blending method - Mingchun Bi; Yuning Liang; Weimeng Chi; Hongya Liu; Ying Chen (Chemical Engineering Journal, 2024)

On the Nearshore Significant Wave Height Inversion from Video Images Based on Deep Learning - Chao Xu; Rui Li; Wei Hu; Peng Ren; Yanchen Song; Haoqiang Tian; Zhiyong Wang; Weizhen Xu; Yuning Liu (Journal of Marine Science and Engineering, 2024)
Accurate observation of nearshore waves is crucial for coastal safety. In this study, the feasibility of extracting wave information from wave video images captured by shore-based cameras using deep learning methods was explored, focusing on inverting nearshore significant wave height (SWH) from instantaneous wave video images. The accuracy of deep learning models in classifying wind wave and swell wave images was investigated, providing reliable classification results for SWH inversion research. A classification network named ResNet-SW for wave types with improved ResNet was proposed. On this basis, the impact of instantaneous wave images, meteorological factors, and oceanographic factors on SWH inversion was evaluated, and an inversion network named Inversion-Net for SWH that integrates multiple factors was proposed. The inversion performance was significantly enhanced by the specialized models for wind wave and swell. Additionally, the inversion accuracy and stability were further enhanced by improving the loss function of Inversion-Net. Ultimately, time series inversion results were synthesized from the outputs of multiple models; the final inversion results yielded a mean absolute error of 0.04 m and a mean absolute percentage error of 8.52%. Despite certain limitations, this method can still serve as a useful alternative for wave observation.

Centrifuge model tests and numerical simulation on ground-borne vibration propagating and vibration reduction scheme for tunnel inner structure - Zhenghao Liu; Xianfeng Ma; Junyu Chi; Yuning Chen; Chen Wang (Tunnelling and Underground Space Technology, 2024)

Assessing the formation and stability of paddy soil aggregate driven by organic carbon and Fe/Al oxides in rice straw cyclic utilization strategies: Insight from a six-year field trial - Wenqi Gu; Yuning Wang; Yuanyuan Sun; Zifan Liu; Wenjia Wang; Di Wu; Yuxue Zhang; Wen Sun; Xin Wang; Zhibo Feng; Weiming Zhang; Wenfu Chen (Science of The Total Environment, 2024)

MFNet: Multi-scale feature enhancement networks for wheat head detection and counting in complex scene - Yurong Qian; Yugang Qin; Hongyang Wei; Yiguo Lu; Yuning Huang; Peng Liu; Yingying Fan (Computers and Electronics in Agriculture, 2024)

Machine learning reveals the influence of the Changbaishan mantle plume sourced from the mantle transition zone on Cenozoic intraplate magmatism in NE China - Yuning Qi; Huan Chen; Sensen Wu; Takeshi Kuritani; Zhenhong Du; Qunke Xia; Renyi Liu (Chemical Geology, 2024)

A New Prediction Model for Cutting Depth of Hard Rock Using High-Pressure Water Jets - Fuwei Liu; Yansen Wang; Xin Huang; Guoxuan Song; Yuning Wang (Rock Mechanics and Rock Engineering, 2024)

DNN–GA–RF prediction model for rock strength indicators based on sound level and drilling parameters - Zhenghao Liu; Weida Wang; Yuning Chen; Shaoshuai Shi; Junjie Wang; Ruijie Zhao (Bulletin of Engineering Geology and the Environment, 2024)

Ceratophyllum demersum alleviates microplastics uptake and physiological stress responses in aquatic organisms, an overlooked ability - Weihong Zhao; Xirui Zheng; Jintao Liu; Yanming Sui; Yuning Wang; Pan Luo; Xi Zhu; Wenjing Wu; Wen Gu; Xingyu Liu (Journal of Hazardous Materials, 2024)

Perspectives on the highly selective oxidation of copper-mediated C3N4-BiVO4 organic-inorganic hybrid catalysts and the efficient generation of reactive oxygen species - Qian Luo; Yue Chen; Yanjun Zhao; Shan He; Shirui Lv; Yuning Ma; Xintong Liu (Chemical Engineering Journal, 2024)

Enhancing the electrochemical activation kinetics of V2O3 for high-performance aqueous zinc-ion battery cathode materials - Yuexin Liu; Chenlong Gao; Yuning Sun; Xuxia Hao; Zhengjie Pi; Menghao Yang; Xiaoli Zhao; Kefeng Cai (Chemical Engineering Journal, 2024)

In situ conversion of ZnO anchored on porous carbon foams to antiflexible ZIF-8-X (X = Co or NH2) for sieving linear and mono-branched hexane isomers - Xufei Li; Yankang Zhou; Weiqiu Huang; Xinya Wang; Yuning Li; Lipei Fu; Jing Zhong; Lin Liu (Chemical Engineering Journal, 2024)

ENSO-driven hydroclimate changes in central Tibetan Plateau since middle Holocene: Evidence from Zhari Namco’s lake sediments - Changrun Wu; Guangxin Liu; Lu Cong; Xiangzhong Li; Xiangjun Liu; Yuning Liu; Deyan Wu; Yuyan Zhang; Die Bai (Quaternary Science Reviews, 2024)

Designing and fabricating a neoteric immobilized Z-scheme V2O5/FeVO4/430-stainless steel foil photocatalyst composite film for tetracycline degradation with synchronous hydrogen production - Yuning Tu; Ying Liu; Shengwei Chi; Ying Tian; Jiaqi Dang; Taiyu Jin; Dawei Fang; Jun Wang (Journal of Environmental Chemical Engineering, 2024)

The Characteristics of Degradation of Enrofloxacin by Vis / BC-BiOI / PMS Photocatalytic System Based on BiOI-Modified Biochar - Yutong Xiang; Bin Tan; Meng Li; Yuning Liu; Xiangyu Liu; Yuwei Ding; Bing Lin; Qian Zhang (Water, Air, & Soil Pollution, 2024)

Self-supporting oxygen vacancy-rich α-MnO2 nanowire/few-layer graphite/SWNT bundle composite film for high-performance flexible aqueous zinc-ion battery cathode - Yuning Sun; Yuexin Liu; Zhongqiang Wang; Xiaoli Zhao; Kefeng Cai (Chemical Engineering Journal, 2024)

Fast and efficient in-situ construction of low crystalline PEDOT-intercalated V2O5 nanosheets for high-performance zinc-ion battery - Yuexin Liu; Tongde Wang; Yuning Sun; Mingcheng Zhang; Guohua Gao; Jinhu Yang; Kefeng Cai (Chemical Engineering Journal, 2024)

Detection of two homologous major QTLs and development of diagnostic molecular markers for sucrose content in peanut - Zhihui Wang; Yue Zhang; Dongxin Huai; Yuning Chen; Xin Wang; Yanping Kang; Liying Yan; Huifang Jiang; Kede Liu; Yong Lei; Boshou Liao (Theoretical and Applied Genetics, 2024)

Improving Water Quality in a Sea Bay by Connecting Rivers on Both Sides of a Harbor - Yuning Chi; Wenming Zhang; Yanling Liu; Xiaoyu Zhang; Wanqing Chi; Bing Shi (Journal of Marine Science and Engineering, 2024)
Improving water quality is imperative for many sea bays, including Laizhou Bay, China, to achieve sustainable marine development. In 2010, two 17.3 km long sand-retaining embankments were built in southwestern Laizhou Bay, which weakened the nearshore hydrodynamics and seriously impacted the water quality. To mitigate this issue, this study proposes connecting the two rivers on both sides of the embankments to improve the hydrodynamics and thus water exchange in the sea bay. The effectiveness was examined with a numerical model using Mike 21, which was validated for both tidal current velocity and direction at six monitoring locations in the sea bay. The results show that over 53% of the core research area displays an increase (0.0–0.4 m/s) in tidal current speed after the connection, primarily in and around the Haihengwei Fishing Port. Meanwhile, the Eulerian residual currents in the Haihengwei Fishing Port, Mi River estuary and Bailang River estuary become substantially larger (with a maximum increase of 0.16 m/s). In addition, the net transport distance of particles released near the connection increases by up to 39.89 km in one month. Overall, this case study demonstrates that connecting rivers next to a harbor can effectively improve hydrodynamics and thus improve water quality in the bay.

Change of soil bacterial communities in chemically stabilized chromium contaminated soils in an accelerated aging experiment - Linying Yao; Yuning He; Peng Zhao; Zhihao Xie; Longfei Jiang; Danni Li; Yueqiao Liu; Rui Ma; Jianli Jia; Dayi Zhang (Journal of Environmental Chemical Engineering, 2024)

Identification of QTLs associated with very-long chain fatty acid (VLCFA) content via linkage mapping and BSA-seq in peanut - Xiaomeng Xue; Jianguo Li; Jie Wu; Meiling Hu; Nian Liu; Liying Yan; Yuning Chen; Xin Wang; Yanping Kang; Zhihui Wang; Huifang Jiang; Yong Lei; et al. (Theoretical and Applied Genetics, 2024)

Changes in properties of human milk under different conditions of frozen storage - Kaibo Wang; Yanfeng Zhao; Sijia Song; Yingying Lin; Yujia Luo; Yafei Zhang; Yi Xue; Wusun Li; Yuning Zhang; Yao Lu; Heng Quan; Hao Zhang; et al. (Food Research International, 2024)

Co-exposure to molybdenum and cadmium evokes necroptosis and decreases apoptosis in duck myocardium - Hang Liu; Xueyan Dai; Shiwen Xu; Huiling Guo; Jiamei Zhu; Sunan Wang; Yuning Wu; Caiying Zhang (Science of The Total Environment, 2023)

High heat Resistance, Strength, and toughness of epoxy resin with cellulose nanofibers and structurally designed ionic liquid - Chunhong Zhang; Jingsong Cui; Wenbo Sui; Yuning Gong; Hao Liu; Yuhui Ao; Lei Shang (Chemical Engineering Journal, 2023)

Green to health: The impact of environmental regulation on health status - Junbing Xu; Yuning Wang; Wei Liu (Sustainable Cities and Society, 2023)

Could continuous rice cropping increase soil fertility and rice productivity by rice straw carbonized utilization in cold areas? — A 6-year field-located trial - Di Wu; Zhibo Feng; Wenqi Gu; Yuning Wang; Zifan Liu; Wenjia Wang; Yuxue Zhang; Weiming Zhang; Wenfu Chen (Environmental Science and Pollution Research, 2023)

A method of matching the combustion chamber diameter based on spray characteristics for lateral swirl combustion system - Jiang Chang; Xiangrong Li; Yanlin Chen; Weihua Zhao; Liang Xie; Dong Liu; Yuning Kang (Fuel, 2023)

Experimental studies on the particulate matter emission characteristics of a lateral swirl combustion system for direct injection diesel engines - Dong Liu; Xiangrong Li; Liang Xie; Jiang Chang; Yuning Kang; Zhi Zhang (Environmental Pollution, 2023)

Sediment yield in the Lower Jinsha River Basin, China: Controlling factors and spatiotemporal patterns - Yuning Tan; Huaixiang Liu; Yongjun Lu (CATENA, 2023)

Identification of ammonium source for groundwater in the piedmont zone with strong runoff of the Hohhot Basin based on nitrogen isotope - Jinyuan Liu; Jiongliang Yuan; Yilong Zhang; Hengxing Zhang; Yiqing Luo; Yuning Su (Science of The Total Environment, 2023)

Interplay of flow and bed morphology caused by pool-riffle sequence formation without upstream sediment supply in gravel-bed rivers - Jiyi Gu; Huaixiang Liu; Yongjun Lu; Tingjie Huang; Yuning Tan; Mingcheng Zhu (CATENA, 2023)

Sequence Stratigraphy, Sedimentology, and Reservoir Characteristics of the Middle Cretaceous Mishrif Formation, South Iraq - Leifu Zhang; Wenqi Zhang; Yong Li; Benbiao Song; Dawang Liu; Ya Deng; Jiacheng Xu; Yuning Wang (Journal of Marine Science and Engineering, 2023)
The Cenomanian–Early Turonian Mishrif Formation is a great contributor to oil production in Iraq. Integrating petrographic, mineralogical, and wireline logging data from 52 wells, this study provides an improved understanding of the sequence stratigraphy, depositional evolution, and reservoir characteristics of the Mishrif Formation in the Mesopotamian Basin, south Iraq. Five types of facies associations are classified: lagoon, shoal, rudist bioherm, shallow marine, and deep marine. Such a classification allows convenient differentiation and interpretation of wireline logs. A sequence stratigraphic framework including five third-order sequences (Mhf 1 to Mhf 5) for the Mishrif Formation is established mainly using wireline logging data of close-distance wells, with the aid of cores and thin sections. Two end-member depositional evolution stages are recognized, from clinoform-like progradational shoal complexes in Mhf 1 within a shallow marine environment, to tidal channels in Mhf 2–3 within a lagoon environment. For Mhf 4–5, abrupt changes in facies associations from north to south indicate the development of an intra-shelf basin where organic-rich mudstones directly overlie the shallow marine grainstone shoals and lagoonal wackestones. Reservoir characteristics and compartmentalization are directly controlled by the sequence stratigraphic framework. Sequence boundaries are featured by wackestones and mudstones overprinted by cementation; they are regionally correlatable and work as regional barriers. Shoal complexes in Mhf 1 and tidal channels in Mhf 2–3 are the main reservoir units. Mudstones and wackestones are intra-reservoir baffles and become more frequently developed towards the south, reflecting the increasing water depth towards south. The characterization of the tidal channels, clinoform-like shoals, and intrashelf basinal deposits in the current study could benefit later development of the Mishrif Formation.

Exploring the spatially heterogeneous impacts of industrial agglomeration on regional sustainable development capability: evidence from new energy industries - Yueqi Yu; Zhouzhou Lin; Dongxia Liu; Yuning Hou (Environment, Development and Sustainability, 2023)

Occurrence of halogenated methanesulfonic acids in water and sediment from the Hangzhou Bay, China - Fang Tao; Yujia Tan; Junwei Dai; Congrui Lu; Yadong Sha; Yi Liu; Xinxing Zhou; Qingele Hasi; Zhemin Shen; Yuning Ma (Environmental Research, 2023)

Identification of a stable major sucrose-related QTL and diagnostic marker for flavor improvement in peanut - Weitao Li; Li Huang; Nian Liu; Yuning Chen; Jianbin Guo; Bolun Yu; Huaiyong Luo; Xiaojing Zhou; Dongxin Huai; Weigang Chen; Liying Yan; Xin Wang; et al. (Theoretical and Applied Genetics, 2023)

Highly efficient base editing in rabbit by using near-PAMless engineered CRISPR/Cas9 variants - Zhongtian Zhang; Xinyu Wu; Jie Yang; Xin Liu; Ruonan Liu; Yuning Song (Science China Life Sciences, 2023)

Single and combined toxicity assessment of primary or UV-aged microplastics and adsorbed organic pollutants on microalga Chlorella pyrenoidosa - Wei Song; Caixia Fu; Yuning Fang; Zhuoyue Wang; Ji Li; Xiaolei Zhang; Kalpana Bhatt; Lu Liu; Ningjie Wang; Fang Liu; Shunni Zhu (Environmental Pollution, 2023)

Magnetically-oriented porous hydrogel advances wearable electrochemical solidoid sensing heavy metallic ions - Wanxin Tang; Zhen Gu; Yao Chu; Jian Lv; Li Fan; Xinling liu; Feng Wang; Ye Ying; Jian Zhang; Yuning Jiang; Jiaying Cao; Anni Zhu; et al. (Chemical Engineering Journal, 2023)

Structural elucidation approaches in carbohydrates: A comprehensive review on techniques and future trends - Yuning Liu; Yajun Huang; Ruiyu Zhu; Mohamed A. Farag; Esra Capanoglu; Chao Zhao (Food Chemistry, 2023)

Island-like CeO2 decorated LiMn2O4: Surface modification enhancing electrochemical lithium extraction and cycle performance - Guiling Luo; Xiaowei Li; Linlin Chen; Yuning Zhang; Jun Gu; Yanhong Chao; Wenshuai Zhu; Zhichang Liu; Chunming Xu (Chemical Engineering Journal, 2023)

Antibacterial effect of Cu2O/TiO2 photocatalytic composite on Pseudomonas marginalis pv. marginalis - Ying Jiang; Mengna Ding; Lang Liu; Jianguo Cao; Liuhong Chen; Guozheng Huang; Yuning Huo; Xiling Dai (Archives of Microbiology, 2022)

Investigation of the mechanism of Shen Qi Wan prescription in the treatment of T2DM via network pharmacology and molecular docking - Piaopiao Zhao; Xiaoxiao Zhang; Yuning Gong; Weihua Li; Zengrui Wu; Yun Tang; Guixia Liu (In Silico Pharmacology, 2022)

Detection of a major QTL and development of KASP markers for seed weight by combining QTL-seq, QTL-mapping and RNA-seq in peanut - Zhihui Wang; Liying Yan; Yuning Chen; Xin Wang; Dongxin Huai; Yanping Kang; Huifang Jiang; Kede Liu; Yong Lei; Boshou Liao (Theoretical and Applied Genetics, 2022)

Correction to: Application of Metabolomics to the Discovery of Biomarkers for Ischemic Stroke in the Murine Model: a Comparison with the Clinical Results - Jinjing Jia; Hangyao Zhang; Xiaoyi Liang; Yuning Dai; Lihe Liu; Kaiwen Tan; Ruohan Ma; Jiahuan Luo; Yi Ding; Chaofu Ke (Molecular Neurobiology, 2022)

Application of Metabolomics to the Discovery of Biomarkers for Ischemic Stroke in the Murine Model: a Comparison with the Clinical Results - Jinjing Jia; Hangyao Zhang; Xiaoyi Liang; Yuning Dai; Lihe Liu; Kaiwen Tan; Ruohan Ma; Jiahuan Luo; Yi Ding; Chaofu Ke (Molecular Neurobiology, 2021)

The Innate Immune Response to Infection by Polyascus gregaria in the Male Chinese Mitten Crab (Eriocheir sinensis), Revealed by Proteomic Analysis - Yanping Yang; Fengjiao Ma; Juanjuan Dong; Lianxing Li; Ping Ren; Yuning Zhang; Yatao Wu; Yinping Wang; Kai Liu; Fang Zhang (Fishes, 2021)
The Chinese mitten crab (Eriocheir sinensis) is a representative catadromous invertebrate of the Yangtze River and a commercial species widely cultivated in China. Both cultivated and wild crabs suffer from a variety of parasites and pathogens, which can result in catastrophic economic losses in aquaculture revenue. Polyascus gregaria, a parasitic barnacle with a highly derived morphology, is specialized in invading these crabs. This study examines the immunological mechanism in E. sinensis infected with P. gregaria. Tandem mass tags (TMT), a specialized method of mass-spectrometry, was used to analyze the infection by P. gregaria resistance at the protein level. In the hepatopancreas of infected crabs, 598 proteins differentially expressed relating to physiological change, of which, 352 were upregulated and 246 were downregulated. Based on this differential protein expression, 104 GO terms and 13 KEGG pathways were significantly enriched. Differentially expressed proteins, such as ATG, cathepsin, serpin, iron-related protein, Rab family, integrin, and lectin, are associated with the lysosome GO term and the autophagy-animal KEGG pathways, both of which likely relate to the immune response to the parasitic P. gregaria infection. These results show the benefit of taking a detailed, protein-level approach to understanding the innate immune response of aquatic invertebrates to macroparasite infection.

Research on a new cationic polyacrylamide (CPAM) with a cationic microblock structure and its enhanced effect on sludge condition and dewatering - Yuning Chen; Xuhao Li; Wang Zizeng; Li Feng; Jiehong Xie; Zeluan Lin; Zhihong Xu; Bingzhi Liu; Xiang Li; Huaili Zheng (Environmental Science and Pollution Research, 2021)

Efficient and high-fidelity base editor with expanded PAM compatibility for cytidine dinucleotide - Zhiquan Liu; Siyu Chen; Yingqi Jia; Huanhuan Shan; Mao Chen; Yuning Song; Liangxue Lai; Zhanjun Li (Science China Life Sciences, 2021)

A microblock structure type of anionic flocculant for hematite wastewater treatment: template copolymerization mechanism and enhanced flocculation effect - Li Feng; Xuhao Li; Zizeng Wang; Bingzhi Liu; Yuning Chen; Huaili Zheng (Environmental Science and Pollution Research, 2021)

Genetic diversity analysis for narrow-leafed lupin (Lupinus angustifolius L.) by SSR markers - Yishan Ji; Rong Liu; Jinguo Hu; Yuning Huang; Dong Wang; Guan Li; Md. Mosiur Rahman; Hongyan Zhang; Chenyu Wang; Mengwei Li; Tao Yang; Xuxiao Zong (Molecular Biology Reports, 2020)

Discovery of two novel and adjacent QTLs on chromosome B02 controlling resistance against bacterial wilt in peanut variety Zhonghua 6 - Huaiyong Luo; Manish K. Pandey; Ye Zhi; Huan Zhang; Siliang Xu; Jianbin Guo; Bei Wu; Haiwen Chen; Xiaoping Ren; Xiaojing Zhou; Yuning Chen; Weigang Chen; et al. (Theoretical and Applied Genetics, 2020)
Key message Two novel and adjacent genomics and candidate genes for bacterial wilt resistance were identified on chromosome B02 in peanut variety Zhonghua 6 using both traditional QTL mapping and QTL-seq methods. Abstract Peanut ( Arachis hypogaea ) is an important oilseed crop worldwide. Utilization of genetic resistance is the most economic and effective approach to control bacterial wilt, one of the most devastating plant diseases, in peanut production. To accelerate the genetic improvement of bacterial wilt resistance (BWR) in peanut breeding programs, quantitative trait locus (QTL) mapping has been conducted for two resistant varieties. In this context, we deployed linkage mapping as well as sequencing-based mapping approach, QTL-seq, to identify genomic regions and candidate genes for BWR in another highly resistant variety Zhonghua 6. The recombination inbred line population (268 progenies) from the cross Xuhua 13 × Zhonghua 6 was used in BWR evaluation across five environments. QTL mapping using both SSR- and SNP-based genetic maps identified a stable QTL ( qBWRB02-1 ) on chromosome B02 with 37.79–78.86% phenotypic variation explained (PVE) across five environments. The QTL-seq facilitated further dissection of qBWRB02-1 into two adjacent genomic regions, qBWRB02-1-1 (2.81–4.24 Mb) and qBWRB02-1-2 (6.54–8.75 Mb). Mapping of newly developed Kompetitive allele-specific PCR (KASP) markers on the genetic map confirmed their stable expressions across five environments. The effects of qBWRB02-1-1 (49.43–68.86% PVE) were much higher than qBWRB02-1-2 (3.96–6.48% PVE) and other previously reported QTLs. Nineteen putative candidate genes affected by 49 non-synonymous SNPs were identified for qBWRB02-1-1 , and ten of them were predicted to code for disease resistance proteins. The major and stable QTL qBWRB02-1-1 and validated KASP markers could be deployed in genomics-assisted breeding (GAB) to develop improved peanut varieties with enhanced BWR.

MicroRNA-498 inhibits the proliferation, migration and invasion of gastric cancer through targeting BMI-1 and suppressing AKT pathway - Dong You; Dawei Wang; Peiji Liu; Yuning Chu; Xueying Zhang; Xueli Ding; Xiaoyu Li; Tao Mao; Xue Jing; Zibin Tian; Yinghua Pan (Human Cell, 2020)

High-resolution mapping of a major and consensus quantitative trait locus for oil content to a ~ 0.8-Mb region on chromosome A08 in peanut (Arachis hypogaea L.) - Nian Liu; Jianbin Guo; Xiaojing Zhou; Bei Wu; Li Huang; Huaiyong Luo; Yuning Chen; Weigang Chen; Yong Lei; Yi Huang; Boshou Liao; Huifang Jiang (Theoretical and Applied Genetics, 2020)
Key message ddRAD-seq-based high-density genetic map comprising 2595 loci identified a major and consensus QTL with a linked marker in a 0.8-Mb physical interval for oil content in peanut. Abstract Enhancing oil content is an important breeding objective in peanut. High-resolution mapping of quantitative trait loci (QTLs) with linked markers could facilitate marker-assisted selection in breeding for target traits. In the present study, a recombined inbred line population (Xuhua 13 × Zhonghua 6) was used to construct a genetic map based on double-digest restriction-site-associated DNA sequencing (ddRAD-seq). The resulting high-density genetic map contained 2595 loci, and spanned a length of 2465.62 cM, with an average distance of 0.95 cM/locus. Seven QTLs for oil content were identified on five linkage groups, including the major and stable QTL qOCA08.1 on chromosome A08 with 10.14–27.19% phenotypic variation explained. The physical interval of qOCA08.1 was further delimited to a ~ 0.8-Mb genomic region where two genes affecting oil synthesis had been annotated. The marker SNPOCA08 was developed targeting the SNP loci associated with oil content and validated in peanut cultivars with diverse oil contents. The major and stable QTL identified in the present study could be further dissected for gene discovery. Furthermore, the tightly linked marker for oil content would be useful in marker-assisted breeding in peanut.

Review of Chinese atmospheric science research over the past 70 years: Synoptic meteorology - Zhiyong Meng; Fuqing Zhang; Dehai Luo; Zhemin Tan; Juan Fang; Jianhua Sun; Xueshun Shen; Yunji Zhang; Shuguang Wang; Wei Han; Kun Zhao; Lei Zhu; et al. (Science China Earth Sciences, 2019)

Chromosomes A07 and A05 associated with stable and major QTLs for pod weight and size in cultivated peanut (Arachis hypogaea L.) - Huaiyong Luo; Jianbin Guo; Xiaoping Ren; Weigang Chen; Li Huang; Xiaojing Zhou; Yuning Chen; Nian Liu; Fei Xiong; Yong Lei; Boshou Liao; Huifang Jiang (Theoretical and Applied Genetics, 2018)